Addition of isatuximab to lenalidomide, bortezomib, and dexamethasone as induction therapy for newly diagnosed, transplantation-eligible patients with multiple myeloma (GMMG-HD7): part 1 of an open-label, multicentre, randomised, active-controlled, phase 3 trial - Goldschmidt, Hartmut; Mai, Elias K.; Bertsch, Uta; Fenk, Roland; Nievergall, Eva; Tichy, Diana; Besemer, Britta; Dürig, Jan; Schroers, Roland; von Metzler, Ivana; Hänel, Mathias; Mann, Christoph; et al. (The lancet. Haematology, 2022)
Background - Anti-CD38 monoclonal antibodies have consistently shown increased efficacy when added to standard of care for patients with multiple myeloma. We aimed to assess the efficacy of isatuximab in addition to lenalidomide, bortezomib, and dexamethasone in patients with newly diagnosed transplantation-eligible multiple myeloma. - Methods - This open-label, multicentre, randomised, active-controlled, phase 3 trial was done at 67 academic and oncology practice centres in Germany. This study is ongoing and divided into two parts; herein, we report results from part 1. Eligible patients were aged 18-70 years; had a confirmed diagnosis of untreated multiple myeloma requiring systemic treatment and a WHO performance status of 0-2; and were eligible for induction therapy, high-dose melphalan and autologous haematopoietic stem-cell transplantation, and maintenance treatment. Patients were randomly assigned (1:1) to receive three 42-day cycles of induction therapy either with isatuximab plus lenalidomide, bortezomib, and dexamethasone (isatuximab group) or lenalidomide, bortezomib, and dexamethasone alone (control group) using a web-based system and permuted blocks. Patients in both groups received lenalidomide (25 mg orally on days 1-14 and 22-35), bortezomib (1·3 mg/m2 subcutaneously on days 1, 4, 8, 11, 22, 25, 29, and 32), and dexamethasone (20 mg orally on days 1-2, 4-5, 8-9, 11-12, 15, 22-23, 25-26, 29-30, and 32-33). Isatuximab was given as 10 mg/kg intravenously on days 1, 8, 15, 22, and 29 of cycle 1 and on days 1, 15, and 29 of cycles 2 and 3. The primary endpoint was minimal residual disease (MRD) negativity assessed by flow cytometry, in the intention-to-treat (ITT) population. This study is registered with ClinicalTrials.gov, NCT03617731. - Findings - Between Oct 23, 2018, and Sep 22, 2020, 660 patients were included in the ITT analysis (331 in the isatuximab group and 329 in the control group). 654 (99%) patients were White, two were African, one was Arabic, and three were Asian. 250 (38%) were women and 410 (62%) were men. The median age was 59 years (IQR 54-64). MRD negativity after induction therapy was reached in 166 (50%) patients in the isatuximab group versus 117 (36%) in the control group (OR 1·82 [95% CI 1·33-2·48]; p=0·00017). Median follow-up time from start to end of induction therapy was 125 days (IQR 125-131) versus 125 days (125-132). At least one grade 3 or 4 adverse event occurred in 208 (63%) of 330 patients versus 199 (61%) of 328 patients. Neutropenia of grade 3 or 4 occurred in 77 (23%) versus 23 (7%) patients and infections of grade 3 or 4 occurred in 40 (12%) versus 32 (10%) patients. Among 12 deaths during induction therapy, one death due to septic shock in the isatuximab group and four deaths (one cardiac decompensation, one hepatic and renal failure, one cardiac arrest, and one drug-induced enteritis) in the control group were considered treatment-related. - Interpretation - Addition of isatuximab to lenalidomide, bortezomib, and dexamethasone for induction therapy improved rates of MRD negativity with no new safety signals in patients with newly diagnosed transplantation-eligible multiple myeloma. - Funding - Sanofi and Bristol Myers Squibb (Celgene).